The Muslim Minority Movement in Southmost Thailand: From Periphery to the Centre - Ahmad Suaedy (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2010)
This article, which focuses on observing individual and group actors in the social movement in South Thailand in a way that does not neglect the important contributions made by political actors as well as. By the insurgency and separatist movement, contends that insurgency, separatism, and violence are no longer the typical choice for those who strive for fundamental human rights in the Thai nation-state. Unfortunately, however, the central government of the Thai Kingdom has not been very responsive nor has it taken these demands seriously. It has shown a lack of political will in granting these actors more extensive rights as demanded on a global scale by recent developments in human rights and the rethinking of the concept of nationalism and national identity.DOI: 10.15408/sdi.v17i1.467